The effect of jobs on the forms of the villages of Taif Governorate - Alabdali, Maleeha Hamed (Journal of Humanities & Social Sciences, 2023)
This study seeks to identify the functions of the shapes of villages in the southwestern part of Taif Governorate and to identify the natural and human controls affecting those shapes and the pattern of distribution. The study relied on the inductive approach based on monitoring and scrutinizing the reality with the aim of drawing a picture of the patterns of rural settlement in the region. The study used satellite images of the 70 villages in the southwestern part of Taif Governorate. Then, a shape measurement equation was applied to judge the patterns of shapes functions. The study reached several results, including: After applying the shape factor to the rural settlements in the study area, it became clear to us that all the villages of the study area are circular and characterized by their agricultural function, except for the village of Al-Mashaikh, which takes the rectangular shape. It is mixed between agricultural and residential, as well as we find that the transportation road passes through it, which made it take this shape.